Impact of fiber distribution and cyclic loading on the bond behavior of steel-reinforced UHPC. (February 2022) - Shao, Yi; Tich, Katie L.; Boaro, Sandro B.; Billington, Sarah L.
Abstract: Ultra-high performance concrete (UHPC) is a class of concrete materials that exhibits high compressive strength (over 150 MPa) and is seeing increasing applications around the world. Current reinforced UHPC (R/UHPC) bond studies mostly adopt non-flexural setups, i.e., pull-out tests and tension-lap-splice tests. The bond behavior of R/UHPC in flexure remains largely unknown, which is a fundamental aspect of designing R/UHPC flexural elements. Additionally, the impact of fiber distribution and cyclic loading on R/UHPC bond is little understood, which is important for guiding the casting and design of R/UHPC structures especially in earthquake zones. This study experimentally investigates the impact of fiber volume, cast flow direction, and cyclic loading on R/UHPC bond behavior under a simulated flexural stress state. Results from twenty-five beam-end tests are discussed. Specimens cast with flow perpendicular to the bar exhibited a 9%–26% higher bond strength than specimens cast with the flow parallel to the bar due to the resulting higher fiber-bridging capacity across the splitting crack plane. Compared to the monotonically-loaded specimens, cyclic loading minimally impacts R/UHPC bond strength and accelerates bond-degradation after bond softening occurs. Current R/UHPC bond strength prediction methods are evaluated on the test results from this study and the literature. An energy-based R/UHPC bond-slip model is developed. This model captures the cyclic bond degradation of R/UHPC and other types of high-performance fiber-reinforced cementitious composites (HPFRCC) with a mean absolute error under 13%.